How does The Chinese Language Program at Carthage University’s Higher Language Institute of Tunis in Tunisia use the 5C Method to Provide a Multi-Faceted Chinese Language Education for Tunisian Students? 突尼斯迦太基大学高等语言学院汉语语言专业如何使用5C对突尼斯学生进行多方面的汉语教育？ - Hazem, Lynda Ben (Mandarinable: Journal of Chinese Studies, 2025)
To create standards for foreign language instruction in grades K–12, a coalition of four national language organizations—the Council on Foreign Language Teaching in the United States, the Association of French Teachers in the United States, the Association of German Teachers in the United States, and the Association of Spanish and Portuguese Teachers in the United States—was granted funding in 1993. To define content standards for foreign language education, an eleven-member task force representing various languages, program models, levels of instruction, and geographic areas was assigned. The task force disseminated its findings to the general public and the larger profession at every stage of its formation. The resulting document, which defines and defines the role of education, represents an unprecedented agreement among educators, business leaders, the government, and the community. As a multicultural country, the People's Republic of Tunisia began Chinese language education in the 1970s and offered a three-year undergraduate program in Chinese language at Carthage University’s Higher Language Institute of Tunis in Tunisia. The teachers in this major include locals, non-locals, and Chinese. All the teachers have designed a teaching plan together that can provide students with various aspects of Chinese language education. Since Chinese language teaching for said students is a base education process (meaning most of the students do not have a prior Chinese language education), this article will use the 5C plan for Chinese language learning goals in primary and secondary schools across the United States to separately define the content and objectives of this teaching plan, therefore highlighting it’s strengths and potential weaknesses to help better the Chinese education in Tunisia, aiding in the deepening of Sino-Tunisian relations.